2021
DOI: 10.21608/adjc.2021.70445.1094
|View full text |Cite
|
Sign up to set email alerts
|

SIRT-1 and CD44 in the saliva of oral squamous cell carcinoma, dysplastic and non-dysplastic oral leukoplakia

Abstract: Objective:The objective of this study was to investigate the levels of salivary SIRT-1 and CD44 in patients suffering from oral squamous cell carcinoma (OSCC), dysplastic and non-dysplastic oral leukoplakia to assess their potential role as early diagnostic biomarkers for patients with oral leukoplakia and OSCC. Methods: sixty patients were recruited from the outpatient clinic of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…Age and gender did not show any significant association with CD44 expression. Similar results were reported in the studies conducted by Monteiro et al and Wagih et al 22 23 Asian, Caucasian, and African-Americans showed significant overexpression of the CD44 gene expression compared with normal samples. Similar to our study results, Lee et al, observed that OSCC with positive mutant p53 expression displayed enhanced expression of CD44 ( p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Age and gender did not show any significant association with CD44 expression. Similar results were reported in the studies conducted by Monteiro et al and Wagih et al 22 23 Asian, Caucasian, and African-Americans showed significant overexpression of the CD44 gene expression compared with normal samples. Similar to our study results, Lee et al, observed that OSCC with positive mutant p53 expression displayed enhanced expression of CD44 ( p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…A statistically significant overexpression of CD44 was demonstrated in OSCC patients compared with those with leukoplakia and healthy controls. 23 El-Gendi et al reported that papillary thyroid carcinoma (PTC; n = 30) showed higher CD44v6 expression than follicular thyroid carcinoma ( n = 10). 24 On the contrary, downregulation of the CD44 gene was associated with a poor prognosis of laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%